Fuzzy logic controller in quadcopter - Pan, Biyong (2014)
This report presents the findings of implementing fuzzy logic controller in UAV itself. The main focus here is to compare the difference between the conventional PID controller and fuzzy logic controller in terms of stability. UAV possess nonlinear characteristics. PID controller is a type of linear control. Undoubtedly, using a linear controller to control a nonlinear system is bound to have instability issues. However, fuzzy logic controller is a type of nonlinear controller. Logically speaking, using fuzzy controller to control a nonlinear system will yield a better performance. Matlab is used to design the fuzzy controller and was tested with Simulink simulation. The result has shown that fuzzy controller has a better steady state response in accordance to the setpoint over PID controller. Fuzzy controller was also converted to C language and implemented into multiwii source codes. After testing the fuzzy codes on quadcopter, it was found that quadcopter reacts much quicker than the PID controller.